Jamaica - Davis, Nick. (London : Kuperard ; New York, NY : Distributed in the United States and Canada by Random House Distribution Services, 2011)
Provides travelers with information on Jamaica's culture and customs, including a brief history of the country, and discussing local traditions, business practices, values and attitudes, and other related topics.
Land and people -- Values and attitudes -- Customs and traditions -- Making friends -- Family life -- Time out -- Travel, health, and safety -- Business briefing -- Communicating -- Appendix. Some Jamaican English terms.
Includes bibliographical references (page 165) and index.
Keywords: Etiquette -- Jamaica; National characteristics, Jamaican; Jamaica -- Social life and customs; Jamaica -- Civilization -- 21st century; Jamaica -- Guidebooks